Yoga and Qigong for health: two sides of the same coin? - Boaventura, Paula (2022)
Yoga and qigong are ancient mind–body practices used in the East for thousands of years to promote inner peace and mental clarity. Both share breathing techniques and slow movements and are being used as alternative/complementary approaches to the management of disease, especially chronic problems with no effective conventional treatments. However, information comparing the health benefits of both approaches is scarce, and the choice between yoga or qigong practice may only depend on patients’ preferences or practice availability. The aim of the present paper was to overview yoga and qigong use for health benefits under different pathological conditions. Yoga and qigong seem to have similar effects, which might be expected, since both are similar mind–body approaches with the same concept of vital life-force energy and the practice of meditative movements. Problematic research issues within the literature on yoga and qigong are the small sample sizes, use of different styles, significant variance in practice duration and frequency, short duration of intervention effects, and the usage of a non-active control group, thus emphasizing the need for further high-quality randomized trials. Studies comparing yoga and qigong are warranted in order to assess differences/similarities between the two approaches for health benefits.